2012
DOI: 10.1002/ijc.27424
|View full text |Cite
|
Sign up to set email alerts
|

MED12 mutations in uterine fibroids—their relationship to cytogenetic subgroups

Abstract: Recurrent chromosomal alterations are found in roughly 20% of all uterine fibroids but in the majority cytogenetic changes are lacking. Recently, mutations of the gene mediator subcomplex 12 (MED12) have been detected in a majority of fibroids but no information is available whether or not they co-occur with cytogenetic subtypes as, e.g., rearrangements of the genes encoding high mobility group AT-hook (HMGA) proteins. In a total of 80 cytogenetically characterized fibroids from 50 patients, we were not only a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
173
7
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 193 publications
(195 citation statements)
references
References 41 publications
13
173
7
2
Order By: Relevance
“…Some of these rearrangements have been reported to co-occur with MED12 mutations, suggesting that a subset of HMGA1 rearrangements are secondary events (7). Leiomyomas also may harbor recurrent deletions and rearrangements of 7q22, 22q, and 1p (8)(9)(10)(11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these rearrangements have been reported to co-occur with MED12 mutations, suggesting that a subset of HMGA1 rearrangements are secondary events (7). Leiomyomas also may harbor recurrent deletions and rearrangements of 7q22, 22q, and 1p (8)(9)(10)(11).…”
mentioning
confidence: 99%
“…Leiomyomas also may harbor recurrent deletions and rearrangements of 7q22, 22q, and 1p (8)(9)(10)(11). These deletions co-occur with other genetic alterations and may be secondary driver events, often present only in a subpopulation of tumor cells (4,7,8,(11)(12)(13).…”
mentioning
confidence: 99%
“…They also observed that significantly high levels of wingless-type MMTV integration site family member 4 (WNT4) is expressed in leiomyomas with MED12 mutations (Markowski et al, 2012). These results suggest that the MED12 mutation might be involved in the activation of the Wnt pathway that activates β-catenin, which is known to cause leiomyoma-like lesions in a mouse model.…”
Section: Med12 Mutations and Uterine Leiomyomamentioning
confidence: 92%
“…It has been reported that in patients suffering from uterine leiomyoma, MED12 mutations are found in stem cells, which leads to unlimited growth and tumor. The mutation sites in MED12 are located in the second exon (Makinen et al, 2011a(Makinen et al, , 2011bJe et al, 2012;Markowski et al, 2012). It was recently reported that the second exon mutation occurs in 52.2% of uterine fi broid patients while the mutation is not found in other tumors (Je et al, 2012), implicating the involvement of MED12 in the disease.…”
Section: Med12 Mutations and Uterine Leiomyomamentioning
confidence: 99%
See 1 more Smart Citation